COMPARISON OF MIDWIFERY EDUCATION-TRAINING AND SERVICES BY SYRIAN MIDWIVES STUDENTS IN SYRIA AND TÜRKİYE - VERİM, Esra; Yavaş ÇELİK, Melike (Göbeklitepe Medical Science Journal, 2025)
This study aims to compare midwifery education and services in Syria and Türkiye through the eyes of Syrian students. Phenomenological case design, one of the qualitative research designs, was used. A questionnaire form including sociodemographic data and semi-structured interview questions were used to collect data. Interviews were conducted face-to-face with 22 Syrian students by the researchers in a calm and quiet environment at a time when the students were available. The themes that emerged from the interviews were compiled from the students' sentences. Content analysis was used in the analysis of the data. The researchers transcribed the voice recordings of the students separately and determined titles for the themes. The determined titles were revealed as a result of the critiques of the two researchers. It was revealed from the student comments that midwifery courses and practices in our country were insufficient, the duration of midwifery education was different from our institution, and education and training in Syria was more disciplined and of higher quality. It was reported by the students that the professional roles of midwives in Syria were more developed than the professional roles of midwives in our country. In summary, 2 main themes were identified. Theme 1. Differences in midwifery education-training between Syria and Türkiye, Theme 2. Differences in midwifery services between Syria and Türkiye. When we looked at the demographic data of the students, 68.2% were 23-26 years old, 77.3% had siblings between 5-11, 90.9% were not married, 63.6% had been in Türkiye for 7-12 years, 54.5% wanted to stay in Türkiye after completing their education, 59.1% lived in a large family, 59.1% had an income equal to their expenses, 31.8% had a middle school or high school graduate, 86.3% had a mother who was not working, 68.2% had a father working. As a result, it was determined that Syrian students viewed the education and training provided in our institution and the professional roles of midwifery as inadequate compared to Syria.